In chronic complete spinal cord injury supraspinal changes detected by quantitative MRI are confined to volume reduction in the caudal brainstem - Hug, Andreas; Wang, Haili; Jende, Johann; Böttinger, Markus; Weber, Marc-André; Weidner, Norbert; Lang, Simone (NeuroImage: Clinical, 2021)
There is much controversy about the potential impact of spinal cord injury (SCI) on brain anatomy and function, which is mirrored in the substantial divergence of findings between animal models and human imaging studies. Given recent advances in quantitative magnetic resonance imaging (MRI) we sought to tackle the unresolved question about the link between the presumed injury associated volume differences and underlying brain tissue property changes in a cohort of chronic complete SCI patients. Using the established computational anatomy methods of voxel-based morphometry (VBM) and voxel-based quantification (VBQ), we performed statistical analyses on grey and white matter volumes as well as on parameter maps indicative for myelin, iron, and free tissue water content in the brain of complete SCI patients (n = 14) and healthy individuals (n = 14). Our regionally unbiased white matter analysis showed a significant volume reduction of the dorsal aspect at the junction between the most rostral part of the spinal cord and the medulla oblongata consistent with Wallerian degeneration of proprioceptive axons in the dorsal column tracts in SCI subjects. This observation strongly correlated with spinal cord atrophy assessed by quantification of the spinal cord cross-sectional area at the cervical level C2/3. These findings suggest that Wallerian degeneration of the dorsal column tracts represents a main contributor to the observed spinal cord atrophy, which is highly consistent with preclinical histological evidence of remote changes in the central nervous system secondary to SCI. Structural changes in other brain regions representing remote changes in the course of chronic SCI could neither be confirmed by conventional VBM nor by VBQ analysis. Whether and how MRI based brain morphometry and brain tissue property analysis will inform clinical decision making and clinical trial outcomes in spinal cord medicine remains to be determined.